Comparative of The Performance of Tillage Pattern Side and Alfa on Rice Field Using Rotary Flow Hand Tractor at Kecamatan Pangkalan Susu - Gunawan Sinaga; Lukman Adlin Harahap; Ainun Rohana (Universitas Sumatera Utara, 2015)
Patterns of land management include the ability of the tratcor to cultivate the land using processing pattern to measure work capacity, efficiency and fuel consumption. The objective of this research was to know the capacity of Quick Boxer G1000 tractor on rice field at Kecamatan Pangkalan Susu. Parameters measured were capacity, fuel consumption, tractor efficiency and analysis of tractor usage. The result showed that treatment pattern affected significantly the capacity, fuel consumption, and tractor efficiency. The highest capacity was found in side pattern Keywords: tractor, rice field, treatment pattern.